FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SENI RUPA SISWA DALAM PROSES PEMBELAJARAN SENI BUDAYA DI KELAS X SMKN 3 SIJUNJUNG - Yahana Suprianto Putri; Ernis Ernis (Universitas Negeri Padang, 2020)
The purpose of this research is to show the factors that effect to motivation in learning fine art by process education art and culture in the class X SMKN 3 Sijunjung. This research use methode qualitative descriptive with observation, interview and documentations. Dana analysis by reducing, data exposing, and verification. The result of this research shows the factors that give effect for motivation of learning as intern factors and extern factors also the condition of learning in the class by a teacher’s fine art educate matter with motivation of learning in process art and culture sub fine art.Keywords: Factors, motivation, fine art